Chemsex drugs on the rise: a longitudinal analysis of the Swiss HIV Cohort Study from 2007 to 2017. Issue 4 (18th December 2019) - Hampel, B; Kusejko, K; Kouyos, RD; Böni, J; Flepp, M; Stöckle, M; Conen, A; Béguelin, C; Künzler‐Heule, P; Nicca, D; Schmidt, AJ; Nguyen, H; et al.
Abstract : Objectives: Chemsex refers to the use of sex‐enhancing drugs among men who have sex with men (MSM) in combination with specific sexual and social behaviours. Longitudinal data on this development and the associated health risks are scarce. Methods: Data on all recreational drugs reported in the Swiss HIV Cohort Study (SHCS) from 2007 to 2017 were collected. Drug use was analysed longitudinally for all drug classes. In addition, potential associations between patient characteristics and the consumption of methamphetamine, γ‐hydroxybutric acid/γ‐butyrolactone (GHB/GBL), 3, 4‐methylenedioxymethamphetamine (MDMA/XTC), cocaine and amphetamine were analysed. Results: We analysed 166 167 follow‐up entries for 12 527 SHCS participants, including 7101 free text field entries containing information about recreational drugs other than cannabis, cocaine and heroin. Overall, we observed a stable percentage (9.0%) of recreational drug use (excluding cannabis, amyl nitrite and prescription drugs). For MSM, however, there was an increase in overall drug use from 8.8% in 2007 to 13.8% in 2017, with particularly large increases for methamphetamine (from 0.2 to 2.4%; P < 0.001) and GHB/GBL (from 1.0 to 3.4%; P < 0.001). The use of each of the potentially sex‐enhancing drugs methamphetamine, GHB/GBL, cocaine, XTC/MDMA and amphetamine was significantly associated with condomless sex with nonsteady partners, and higher prevalences of depression, syphilis and hepatitis C. Conclusions: The significant increase in the use of chemsex drugs among MSM in the SHCS and the strong association with coinfections and depression highlights the need for harm reduction programmes tailored to MSM. According to our results, improving knowledge about recreational drugs is important for all health care professionals working with people living with HIV.